Models of Speech Ontogenesis in Russian Monolinguals and Russian-German Bilinguals - L. V. Moskovkin (Научный диалог, 2023)
The aim of the article is to examine models of speech ontogenesis in Russian monolinguals living in Russia and Russian-German bilinguals living in Germany. The study uses deviations from literary language norms in transcriptions of oral speech from 42 monolinguals and 48 bilinguals, supplemented by speech analysis data reflected in printed sources. Research methods include surveys, interviews, reading phonetically representative texts and picture stories, analysis of deviations from literary language norms, and synthesis of speech data. Two models of speech ontogenesis for monolinguals and four models for bilinguals are described. It is shown that the process of speech ontogenesis proceeds differently among Russian language speakers depending on a) whether it occurs in Russia or abroad, b) which variety of Russian language the speaker uses, c) at what age the foreign speaker of Russian language begins to actively use the language of the majority. It is established that the most important factor preventing the loss of elements of the Russian language in the diaspora is mastery of literary language norms. The dependence of the appearance of interference from the German language on the model of speech ontogenesis is determined.